Physiotherapy on the Biodex Balance System Device is More Effective Than Wobble Board Exercises for Regaining Balance, but not the Lower Limb Muscle Strength, in Stroke Patients - Eglė Lendraitienė; Laura Urbonienė; Daiva Petruševičienė; Rasa Šakalienė (Lithuanian Sports University, 2022)
Background. Balance control and restoration of movements are among the most important rehabilitation goals for stroke survivors. There are many techniques used to restore lost function, but there is little research demonstrating the effectiveness of specific equipment in improving balance. The aim. To compare balance and lower limb muscle strength in stroke patients when applying different methods of physiotherapy. Methods. The study included 40 stroke patients with hemiparesis and impaired balance. The subjects were divided into two groups: the first group (n=20) underwent physiotherapy on the Biodex balance system device (with visual feedback), the second group (n=20) - wobble board exercises. Both groups underwent 45-minute physiotherapy sessions 5 times a week (in total, 20 procedures). The subjects were tested at baseline and after physiotherapy. Balance was evaluated by applying the Best Evaluation Systems Test (BEST), and lower limb muscle strength - by using the Oxford muscle strength scale. Results. Physiotherapy on the Biodex balance system device as well as wobble board exercises improved balance and muscle strength in stroke patients. Furthermore, the balance results of the first group (Biodex) was significantly greater than those of the second group (wobble board). No difference in muscle strength parameters was found between the groups. Conclusion. Physiotherapy using the Biodex balance system device (with visual feedback) was superior to wobble board exercises for improving the balance abilities, but not the lower limb muscle strength, in stroke patients. Keywords: stroke, physiotherapy, Biodex, balance, muscle strength, lower limb.